Exploring the Ideal Role of Women for Peace and Harmony: A Study in the Context of Women’s Lives in Early Islam - Hafiza Ambreen Fatima (AL-IDRAK JOURNAL, 2023)
This essay carefully examines how women find peace, tranquillity and calm in Islam, focusing on patience and family values. It looks closely at how important it is for women to have peace in their lives and how Islamic beliefs emphasise patience and family values. This study digs deep into the Islamic perspective, exploring the significance of sabr (patience) within the Islamic framework. The paper compares Islamic teachings with how cultures and societies interpret these ideas, showing the different ways women use these principles in their lives. It also explores how following these values can affect women's happiness and strength, showing why it's important to understand and accept these principles in today's world. Furthermore, the essay explores the potential implications of these values on women's well-being and empowerment, shedding light on the significance of understanding and embracing these principles within the broader context of modern society. Through this exploration, the research seeks to contribute to a deeper understanding of Islam's role in shaping women's lives and fostering a sense of tranquillity and contentment in the face of life's difficulties.